Late-Onset Cone Photoreceptor Degeneration Induced by R172W Mutation in Rds and Partial Rescue by Gene Supplementation - Conley, Shannon (2007)
PURPOSE: R172W is a common mutation in the human retinal degeneration slow (RDS) gene, associated with a late-onset dominant macular dystrophy. In this study, the authors characterized a mouse model that closely mimics the human phenotype and tested the feasibility of gene supplementation as a disease treatment strategy. METHODS: Transgenic mouse lines carrying the R172W mutation were generated. The retinal phenotype associated with this mutation in a low-expresser line (L-R172W) was examined, both structurally (histology with correlative immunohistochemistry) and functionally (electroretinography). By examining animals over time and with various rds genetic backgrounds, the authors evaluated the dominance of the defect. To assess the efficacy of gene transfer therapy as a treatment for this defect, a previously characterized transgenic line expressing the normal mouse peripherin/Rds (NMP) was crossed with a higher-expresser Rds line harboring the R172W mutation (H-R172W). Functional, structural, and biochemical analyses were used to assess rescue of the retinal disease phenotype. RESULTS: In the wild-type (WT) background, L-R172W mice exhibited late-onset (12-month) dominant cone degeneration without any apparent effect on rods. The degeneration was slightly accelerated (9 months) in the rds(+/−) background. L-R172W retinas did not form outer segments in the absence of endogenous Rds. With use of the H-R172W line on an rds(+/−) background for proof-of-principle genetic supplementation studies, the NMP transgene product rescued rod and cone functional defects and supported outer segment integrity up to 3 months of age, but the rescue effect did not persist in older (11-month) animals. CONCLUSIONS: The R172W mutation leads to dominant cone degeneration in the mouse model, regardless of the expression level of the transgene. In contrast, effects of the mutation on rods are dose dependent, underscoring the usefulness of the L-R172W line as a faithful model of the human phenotype. This model may prove helpful in future studies on the mechanisms of cone degeneration and for elucidating the different roles of Rds in rods and cones. This study provides evidence that Rds genetic supplementation can be used to partially rescue visual function. Although this strategy is capable of rescuing haplo-insufficiency, it does not rescue the long-term degeneration associated with a gain-of-function mutation.